2010
DOI: 10.1158/1078-0432.ccr-09-3191
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Integrated Genomic Classifier for a Novel Agent in Colorectal Cancer: Approach to Individualized Therapy in Early Development

Abstract: Background: A plethora of agents is in early stages of development for colorectal cancer (CRC), including those that target the insulin-like growth factor I receptor (IGFIR) pathway. In the current environment of numerous cancer targets, it is imperative that patient selection strategies be developed with the intent of preliminary testing in the latter stages of phase I trials. The goal of this study was to develop and characterize predictive biomarkers for an IGFIR tyrosine kinase inhibitor, OSI-906, that cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 46 publications
1
96
0
Order By: Relevance
“…According to the global gene expression analysis of NCI-H295A cells, the inhibition of IGF1R with OSI-906 seems to upregulate caspases activity and to induce cell cycle arrest. Gene array analysis conducted on a broad panel of colorectal cancer cell lines 23:6 revealed that OSI-906-sensitive cells present upregulation of the P53 pathway, while resistant cells present MAPK pathway upregulation (Pitts et al 2010). At 6 h of OSI-906 treatment, we observed the upregulation of P53 signaling pathway genes and reduction of genes associated with MAPK pathway activation, suggesting a sensitive profile of the NCI-H295A cell line.…”
Section: Discussionmentioning
confidence: 74%
“…According to the global gene expression analysis of NCI-H295A cells, the inhibition of IGF1R with OSI-906 seems to upregulate caspases activity and to induce cell cycle arrest. Gene array analysis conducted on a broad panel of colorectal cancer cell lines 23:6 revealed that OSI-906-sensitive cells present upregulation of the P53 pathway, while resistant cells present MAPK pathway upregulation (Pitts et al 2010). At 6 h of OSI-906 treatment, we observed the upregulation of P53 signaling pathway genes and reduction of genes associated with MAPK pathway activation, suggesting a sensitive profile of the NCI-H295A cell line.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, these investigators showed that other components of the pathway, such as the adaptor proteins, IRS1 and IRS2, and the ligand, IGF2, have predictive value in these tumor models. A similar study, which aimed to develop and characterize predictive biomarkers for the IGF1R tyrosine kinase inhibitor, OSI-906, in colorectal cancer, also noted that the IGF1R/EGFR/ insulin pathways were dominant in sensitive cells (22).…”
Section: Discussionmentioning
confidence: 89%
“…There is growing interest in identifying predictors of response to anti-IGF1R therapy (20)(21)(22). The aim of this study was to identify biomarkers predictive of clinical efficacy with the IGF1R inhibitor, figitumumab, to help identify patient subgroups that may benefit from this type of targeted treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Since RP11-915H6 and all other most appropriate and available BAC clones spanning this region cover a significant number of neighboring genes around the MST1R locus as compared to WI2-1337B15 and WI2-1244I5 fosmids, and because the probe generated from the combination of these two fosmids gave adequate bright signals, results of RP11-915H6 FISH were omitted here and will be presented elsewhere. Efficiency of the dual probe hybridization was confirmed by FISH on normal lymphocyte described to be prognostic of clinical outcomes and predictive of response to targeted inhibition in cancers, [45][46][47] Table 3). GCN of all three genes by qPCR in GC cell lines was validated with aCGH in NCI-N87 (Fig.…”
Section: Alterations In Mst1r (Ron) Gene By Fishmentioning
confidence: 91%
“…Analysis of GCN alterations in MST1R and MET were performed and cut-off points were applied as previously described for MET, EGFR and IGF1R genes. 45,47,80 Interpretation of HER2/CEP17 FISH was performed as previously described for GEC. 7,73 To our knowledge, the cut off points for MET FISH-positivity has not yet been standardized; FISH studies of MST1R have not yet being reported.…”
Section: Methodsmentioning
confidence: 99%